Human endothelial cell-lymphocyte interaction. Endothelial cells function as accessory cells necessary for mitogen-induced human T lymphocyte activation in vitro. - Ashida, E R (1981)
Mitogen-stimulated human T cell activation is absolutely dependent on the participation of a nonresponding accessory cell. In populations of human peripheral blood mononuclear cells, monocytes function as the requisite accessory cells. The possibility that cultured endothelial cells (EC) might also function as accessory cells was studied by examining the potential of endothelial cells to restore mitogen responsiveness to monocyte-depleted human T cells. Highly purified T cells were prepared by isolating cells rosetting with sheep erythrocytes and removing monocyte contamination by glass adherence and nylon wool column passage. When cultured at low cell density, T cells failed to respond to stimulation with various mitogenic lectins, whereas co-culture with monocytes restored responsiveness. Similarly, EC obtained from umbilical vein, pulmonary artery, and ovarian vein restored the capacity of T cells to respond to mitogens. Mitogen-stimulated T cell activation required viable endothelial cells. Moreover, effective endothelial T cell cooperation appeared to involve the establishment of cell-to-cell contact between EC and responding T cells. Accessory cell function was not a nonspecific property of all tissue culture cells as evidenced by the finding that human foreskin fibroblasts, lung fibroblasts, and HeLa cells were unable to restore responsiveness to monocyte-depleted T cells. These observations indicate that endothelial cells can support the induction of mitogen-induced T cell activation and suggest that cells lining blood vessels may play an active role in the initiation of immune responses in vivo.